TIC em hospitais privados: estudo do uso, do custo e da integração - Brugnolo Filho, Marino (2016)
The thesis studies and analyzes the Information and Communication Technologies (ICT) available in hospitals in Brazil, associated with ANAHP - National Association of Private Hospitals which sponsored the data collection and supported research on two central themes: use and cost; integration and interoperability of ICT. The Organization for Economic Cooperation and Development (OECD), in a study on health ICT, said that if implemented effectively, ICTs could result in improved quality in the delivery of health services, increased safety in patient care and lower costs. To allow comparisons of results and use trusted models, this study adapted the Research Model of IT Usage of GVcia - Applied Information Technology Center at FGV - EAESP and complemented the research tools, using as reference a recent research applied to US, to raise specific data of ICT integration in hospitals. Data collection was carried out for the period 2009-2015 in two stages. The first sent the electronic questionnaire, validated by executives of hospitals and shown in Appendix A. In the second stage, the submitted data were validated and integration aspects have been clarified through interviews. The cost of study and use of ICT resulted in the calculation of various indicators. ICT expenditure and investments in private hospitals amounted to 3.5% of the annual turnover of the sample hospitals while the health sector, in turn, spent and invested 6.4% of annual revenues with ICT implemented. Another novel and important indicator for future studies in the sector is the annual cost of ICT for hospital bed which has remained stable at around $ 39,000 between 2010 and 2014 and fell to $ 36,000 in 2015, equivalent to R $ 120,000 December 2015. Other statistics and indicators presented in this study help to understand the evolution and performance of ICT in the delivery of health services and may be useful in deciding whether ICT will help improve safety and patient care, health professional’s access to data the patient and the necessary line with the Digital Health Model (e-Health), the appropriate costs. The results of this study are comparable to similar American and allow inferring that the technology park in use in the Brazilian private hospitals can leverage the integration of existing systems, allowing line with Digital Health models with the improvement of extended health chain performance the attention to citizens who may be assisted wherever you are, at any time, safely. Management action and investment are the key topics involving integration.